Alternating Hemiplegia: Mitochondrial Dysfunction - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Mitochondrial function in 4 patients with alternating hemiplegia (AH) was evaluated by magnetic resonance spectroscopy of resting muscle at the Montreal Neurological Institute, McGill University, Montreal, Canada.